AZD7442 (Tixagevimab/Cilgavimab) for Post-Exposure Prophylaxis of Symptomatic Coronavirus Disease 2019. (22nd November 2022) - Levin, Myron J; Ustianowski, Andrew; Thomas, Steven; Templeton, Alison; Yuan, Yuan; Seegobin, Seth; Houlihan, Catherine F; Menendez-Perez, Ibrahim; Pollett, Simon; Arends, Rosalinda H; Beavon, Rohini; Dey, Kanika; et al.
Abstract: Background: This phase 3 trial assessed AZD7442 (tixagevimab/cilgavimab) for post-exposure prophylaxis against symptomatic coronavirus disease 2019 (COVID-19). Methods: Adults without prior severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection or COVID-19 vaccination were enrolled within 8 days of exposure to a SARS-CoV-2–infected individual and randomized 2:1 to a single 300-mg AZD7442 dose (one 1.5-mL intramuscular injection each of tixagevimab and cilgavimab) or placebo. Primary end points were safety and first post-dose SARS-CoV-2 reverse-transcription polymerase chain reaction (RT-PCR)–positive symptomatic COVID-19 event before day 183. Results: A total of 1121 participants were randomized and dosed (AZD7442, n = 749; placebo, n = 372). Median (range) follow-up was 49 (5–115) and 48 (20–113) days for AZD7442 and placebo, respectively. Adverse events occurred in 162 of 749 (21.6%) and 111 of 372 (29.8%) participants with AZD7442 and placebo, respectively, mostly mild/moderate. RT-PCR–positive symptomatic COVID-19 occurred in 23 of 749 (3.1%) and 17 of 372 (4.6%) AZD7442- and placebo-treated participants, respectively (relative risk reduction, 33.3%; 95% confidence interval [CI], −25.9 to 64.7; P = .21). In predefined subgroup analyses of 1073 (96%) participants who were SARS-CoV-2 RT-PCR–negative (n = 974, 87%) or missing an RT-PCR result (n = 99, 9%) at baseline, AZD7442 reduced RT-PCR–positive symptomatic COVID-19 by 73.2% (95% CI, 27.1 to 90.1) vs placebo. Conclusions: This study did not meet the primary efficacy end point of post-exposure prevention of symptomatic COVID-19. However, analysis of participants who were SARS-CoV-2 RT-PCR–negative or missing an RT-PCR result at baseline support a role for AZD7442 in preventing symptomatic COVID-19. Clinical Trials Registration . NCT04625972. Abstract : AZD7442 (tixagevimab/cilgavimab) for post-exposure prophylaxis of coronavirus disease 2019 (COVID-19) did not reduce symptomatic COVID-19 in all participants, but did so in participants who were severe acute respiratory syndrome coronavirus 2 reverse-transcription–polymerase chain reaction–negative/missing at baseline.